Reflections on the crisis and labor migration - Barrantes Serrano, Briseida (2019)
Two elements in the foundations of society have determined which are the factors that cause inequality, prejudices, stereotypes and attitudes that have been directed towards the promotion of discrimination that generates its application in different areas of daily life, within the established order and that in this 21st century they have been accentuated. One is the ideological factor and the other is the preponderant economic system. Both come together so that the multitudes of people who migrate from one place to another become victims of xenophobia, as well as hate and intolerance campaigns, which are accentuated depending on ethnic origin, sex, age, etc. Profiting from the thousands of human beings who want to arrive or stay in a destination that fills them with hope, is a double discrimination, so perverse of oppression and exploitation as a result of the weaknesses of public policies that promote the development and generation of decent jobs that reduce the levels of inequality and poverty faced by workers and their families.